Acute myocarditis presenting as acute coronary syndrome: role of early cardiac magnetic resonance in its diagnosis. Issue 16 (23rd November 2010) - Monney, Pierre A; Sekhri, Neha; Burchell, Thomas; Knight, Charles; Davies, Ceri; Deaner, Andrew; Sheaf, Michael; Baithun, Suhail; Petersen, Steffen; Wragg, Andrew; Jain, Ajay; Westwood, Mark; et al.
Abstract : Background: In patients presenting with acute cardiac symptoms, abnormal ECG and raised troponin, myocarditis may be suspected after normal angiography. Aims: To analyse cardiac magnetic resonance (CMR) findings in patients with a provisional diagnosis of acute coronary syndrome (ACS) in whom acute myocarditis was subsequently considered more likely. Methods and results: 79 patients referred for CMR following an admission with presumed ACS and raised serum troponin in whom no culprit lesion was detected were studied. 13% had unrecognised myocardial infarction and 6% takotsubo cardiomyopathy. The remainder (81%) were diagnosed with myocarditis. Mean age was 45±15 years and 70% were male. Left ventricular ejection fraction (EF) was 58±10%; myocardial oedema was detected in 58%. A myocarditic pattern of late gadolinium enhancement (LGE) was detected in 92%. Abnormalities were detected more frequently in scans performed within 2 weeks of symptom onset: oedema in 81% vs 11% (p<0.0005), and LGE in 100% vs 76% (p<0.005). In 20 patients with both an acute (<2 weeks) and convalescent scan (>3 weeks), oedema decreased from 84% to 39% (p<0.01) and LGE from 5.6 to 3.0 segments (p=0.005). Three patients presented with sustained ventricular tachycardia, another died suddenly 4 days after admission and one resuscitated 7 weeks following presentation. All 5 patients had preserved EF. Conclusions: Our study emphasises the importance of access to CMR for heart attack centres. If myocarditis is suspected, CMR scanning should be performed within 14 days. Myocarditis should not be regarded as benign, even when EF is preserved.